2018
DOI: 10.1002/mc.22910
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the molecular effect of a rare missense mutation in BRIP1 associated with inherited breast cancer

Abstract: BRIP1 is a component of the Fanconi Anemia/BRCA pathway responsible for DNA reparation via helicase activity. Some heterozygous variants in BRIP1 could contribute to Hereditary Breast Cancer through a defective DNA repair. The clinical utility of BRIP1 mutations in a familial cancer context is compromised by the conflicting interpretation of "variants of uncertain significance" (VUS). Defining the clinical significance of variants identified in genetic tests is a major challenge; therefore, studies that evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Likewise, FA-associated FANCJ clinical mutations fail to restore ICL resistance, consistent with the role of FANCJ enzyme activity in ICL repair processing (14). While other pathogenic variants that disrupt FANCJ enzyme function, expression, or splicing have been identified (17,20,22,23), the majority of FANCJ sequence changes remain unclassified, thereby limiting clinical utility.…”
Section: Introductionmentioning
confidence: 76%
“…Likewise, FA-associated FANCJ clinical mutations fail to restore ICL resistance, consistent with the role of FANCJ enzyme activity in ICL repair processing (14). While other pathogenic variants that disrupt FANCJ enzyme function, expression, or splicing have been identified (17,20,22,23), the majority of FANCJ sequence changes remain unclassified, thereby limiting clinical utility.…”
Section: Introductionmentioning
confidence: 76%
“…Zhao ( 46 ) reported that MLH1 , MSH2 , MSH6 and PMS1 are present in stage II and III colorectal cancer patients. Velázquez et al ( 47 ) found that BRIP1 gene mutations occurred in inherited breast cancer patients. It was also reported that the association between MSH6 and BRIP1 variants are relevant to oxidative DNA damage in triple negative breast patients ( 48 ).…”
Section: Discussionmentioning
confidence: 99%